Effect of Nigella sativa extract on nasal mucosal inflammation in rats exposed to cigarette smoke - Alamanda, Fathika; Dewi, Anna Mailasari Kusuma; Marliyawati, Dwi; Santosa, Yanuar Iman (Faculty of Medicine, Universitas Islam Sultan Agung (UNISSULA), Indonesia, 2024)
Cigarette smoke contains toxic compounds that can initiate an inflammatory reaction and infiltrate inflammatory cells. The nasal mucosa is the initial part of the respiratory system that comes into contact with irritating chemicals such as cigarettes. Prior studies indicated that Nigella sativa extract (NS) has thymoquinone, a bioactive compound with anti-inflammatory properties. Our study aims to determine the effect of different doses of NS on inflammation of the nasal mucosa in Wistar rats exposed to cigarette smoke. The study employed an experimental post-test-only control group design. Twenty-five Wistar rats were randomly assigned to one of the five groups: negative control (K-), positive control (K+), and three treatment groups of P1, P2, and P3 receiving NS at the dose of 0.5, 1, and 1.5 g/kg bw/day, respectively. All treatment groups and the positive control group were exposed to smoke from 4 cigarettes/day for 28 days. The degree of inflammatory cell infiltration was evaluated using a histological scoring : 0 if normal; 1 if infiltration was less than 1/3; 2 if infiltration was between 1/2 and 2/3, 3 if infiltration of more than 2/3 indicating normal, less than 1/3, 1/3 to 2/3, and more than 2/3, respectively. The degree of inflammatory cell infiltration in group: K(-): 1.00 ±0.00, K(+): 1.00±0.00, P1: 1.00±0.00, P2: 1.00±0.37, and P3: 1.00±0.33. The Kruskal-Wallis test showed a p-value of 0.001, indicating a significant difference. The Mann-Whitney test revealed significant differences between the K+ and P2 groups (p=0.032), K+ and P3 groups (p=0.013), and P1 and P3 groups (p=0.049). In conclusion, NS can decrease the presence of inflammatory cells in the nasal mucosa in Wistar rats exposed to cigarette smoke.